Wrinkle formation in cylindrical thin film–compliant core structures: Numerical simulations and effects of inelastic deformation - Md Al Rifat Anan; Donghyeon Ryu; Yu-Lin Shen (Advances in Mechanical Engineering)
When a thin film bonded to a thick compliant substrate is subject to in-plane compression, wrinkles can develop if the critical state for instability is reached. In various applications the film/substrate system may also take the form of cylindrical fibers, where an axial compressive loading can trigger axisymmetric wrinkles. A straightforward computational approach to simulate such wrinkling behavior is needed for material design, to either prevent wrinkling or to exploit its benefits for flexible device applications. In this work a comprehensive numerical study is undertaken by employing the finite element method. The embedded imperfection approach used previously for planar structures is now applied to the cylindrical film/substrate system to trigger axisymmetric wrinkles. Uniform and reversible elastic wrinkles can be directly predicted, and the wrinkle geometries are verified by available elastic analytical solutions. The effect of initial imperfection location is also examined. We further study plastic yielding and viscoelasticity of the thin film, and examine how the wrinkle configuration may be influenced by inelastic deformation. Yielding transforms the uniform wrinkles into localized deep folds, and this new surface feature is irrecoverable upon unloading. A viscoelastic thin film results in rate-dependent instability behavior, with very slow strain rates favoring localized waveforms. This study has developed a robust computational approach for the prediction of wrinkle initiation and growth in cylindrical structures with a thin film bonded to a soft core. It is demonstrated that material nonlinearity and rate dependency can be incorporated into the model to greatly expand the simulation capabilities.